Experimental and numerical analysis of compression behaviour of 3D printed metal foams. (December 2020) - Ramesh, R; Prasanth, A S; Krishna, R; KoushikSundaram, K; Arul MozhiSelvan, R; Roy, Abhishek
Abstract: This article focuses on comparing the experimental and numerical compressive behaviour of metal foams. The metal foams were initially modelled in three configurations of pore sizes. Each configuration was 3D printed using a laser sintering metal additive manufacturing technique. Subsequently, quasi-static compression tests were conducted and their stress-strain curves were examined to ascertain the proof stress of the three configurations. A numerical simulation of the compressive behaviours of the three foams was then conducted and their results were correlated with those from experimentation to quantify the error in simulation. The compression tests revealed that, the compressive strength was a function of density and porosity of the metal foams. Further, the numerical results of compression behaviours were validated, with less than 5 % deviation from the experimental results for all three foam configurations.